Effects of soluble flavin on heterogeneous electron transfer between surface-exposed bacterial cytochromes and iron oxides. (15th August 2015) - Wang, Zheming; Shi, Zhi; Shi, Liang; White, Gaye F.; Richardson, David J.; Clarke, Thomas A.; Fredrickson, Jim K.; Zachara, John M.
Abstract: Dissimilatory iron-reducing bacteria can utilize insoluble Fe(Mn)-oxides as a terminal electron acceptor under anaerobic conditions. For Shewanella species specifically, evidence suggests that iron reduction is associated with the secretion of flavin mononucleotide (FMN) and riboflavin. However, the exact mechanism of flavin involvement is unclear; while some indicate that flavins mediate electron transfer (Marsili et al., 2008 ), others point to flavin serving as co-factors to outer membrane proteins (Okamoto et al., 2013 ). In this work, we used methyl viologen (MV + )-encapsulated, porin-cytochrome complex (MtrCAB) embedded liposomes (MELs) as a synthetic model of the Shewanella outer membrane to investigate the proposed mediating behavior of microbially produced flavins. The reduction kinetics of goethite, hematite and lepidocrocite (200 μM) by MELs ([MV + ] ∼ 40 μM and MtrABC ⩽ 1 nM) were determined in the presence FMN at pH 7.0 in N2 atmosphere by monitoring the concentrations of MV + and FMN through their characteristic UV–visible absorption spectra. Experiments were performed where (i) FMN and Fe(III)-oxide were mixed and then reacted with the reduced MELs and (ii) FMN was reacted with the reduced MELs followed by addition of Fe(III)-oxide. The redox reactions proceeded in two steps: a fast step that was completed in a few seconds, and a slower one lasting over 400 s. For all three Fe(III)-oxides, the initial reaction rate in the presence of a low concentration of FMN (⩽1 μM) was at least a factor of five faster than those with MELs alone, and orders of magnitude faster than those by FMNH2, suggesting that FMN may serve as a co-factor that enhances electron transfer from outer-membrane c -cytochromes to Fe(III)-oxides. The rate and extent of the initial reaction followed the order of lepidocrocite > hematite > goethite, the same as their reduction potentials, implying thermodynamic control on reaction rate. For LEP, with the highest reduction potential among the three Fe(III)-oxides, its reduction by FMNH2 was completed in less than 10 min, suggesting that FMN was capable of mediating electron transfer to LEP. At higher FMN concentrations (>1 μM), the reaction rates for both steps decreased and varied inversely with FMN concentration, indicating that FMN inhibited the MEL to Fe(III)-oxide electron transfer reaction under these conditions. The implications of the observed kinetic behaviors to flavin-mediated Fe(III)-oxide reduction in natural environments are discussed.